-

arrow , , arrow



<<     >>

121. -130. , .

y = tg2x.122. y = ln(3x + 1).123. y = cos(x2).

y = sin(x2 + 2x).125. y = ctg(3x - 2).126. y = 2x2 + 1.

127. y = 2 - cos3x.128. y = 2 + sin2x.129. y = e2x.

y = (x + 1) /(x - 1).

131. -140. , .

1) y = 4x4 + tgx; 2) y = x1/2 / sinx;

3) y = ctg5x / x3; 4) y = arctg(ex) + tg(arccos(ex)).

1) y = ln(tg(3x + 2)); 2) y = 1 - x2 arcsinx;

3) y = xtgx; 4) y = (x2 - 1) /(x2 + 1).

1) y = arccos(x2) + arcctg(x2); 2) xy = cos(x - y);

3) y = log2(2x + 1); 4) y = 1 - x2 / 1 + x2.

1) y = (2 - 5x) / 2 - 5x + x2; 2) y = ex - y;

3) y = 2 lnx - x; 4) y = sin2 3t, x = cos4 3t.

1) y = (arcsinx) 1 - x; 2) y = cos2 x + tg2x;

3) x3 + y3 - 3xy = 3; 4) x = t - sin2t, y = 1 - cos 2t.

1) y = sin2x/(1 + sin2x); 2) y = 3arctgx + (arctgx) 3,

3) y = (1 + x2) 1 + 2x; 4) y = tg3t, x = cos2 3t.

1) y = 3 -3x + (3x) -3; 2) y = (x - 1) log5(x2 - 1),

3) y = (x2 + 1) x; 4) y = tg(x2/y2).

1) y = ln(lg(log2x)); 2) y = (x2 + x + 1) /(x2 + 1);

3) y = (x + 1) x; 4) ex + y = x - y.

1) y = (x2 + 1) 3 - (x2 - 1) 3; 2) y = (ln5x) /(x4 - 1);

3) y = (tgx) ctgx; 4) x = t ctg(t2), y = t cos2(t2).

1) y = ln(x + x2 + 1); 2) y = x -sin2x;

3) y = 2/(x -1) + 1/(x2 - 1); 4) sin(x + y) + cos(x2 + y2) = 1.

141. -160. , .

141. y = (x2 + 2x + 2) /(2 + x2) .142. y = (4 + x2) /(9 - x2).

143. y = (2 + 3x2) /(1 + x2).144. y = (x3 + 2x2 + 2) /(x2 + 1).

145. y = (x2 + 3x + 5) /(x - 1).146. y = (3x3 - 2) /x.

147. y = (2x2 +3x + 1) /(x - 2).148. y = x3/(x3 + 1).

149. y = (3 - 9x2) /(1 - 9x2).150. y = (x3 + 8) /(x3 - 8).

151. y = x e 2x - 1.152. y = ln(x2 - 9).

153. y = (1 + x2) exp(-x2).154. y = lg(4 + x2).

155. y = exp(2/(1 - x)) .156. y = ln(16 - x2).

157. y = x2 + 1 + 2lnx.158. y = exp(1 + 4x - 2x2).

159. y = (2 + x) exp( - 4 - 4x - x2)).160. y = (1 - x) - 0.5 lg(1 - x).

161. -170. :

y = f(x) , x0;

x = x(t), y = y(t) , t t0.

, . .

161.1 ) y = (9 - x2) /3, x0 = - 3/2; 2) x = 3cost, y = 3 sint, t0 = - /3.

162.1 ) y = 4 - 8x2, x0 = - 1/2; 2) x = 1/2 cost, y = 2 sint, t0 = 5/4.

163.1 ) y = 16 - 4x2, x0 = 1; 2) x = 2 sint, y = 4 cost, t0 = 5/6.

164.1 ) y = 8 - 3x2, x0 = 2; 2) x = 2 2/3 cost, y = 2 2 sint, t0 = /6.

165.1 ) y = 25 - 5x2, x0 = 0.5 5; 2) x = 5 sint, y = 5 cost, t0 = 7/6.

166.1 ) y = (4 - x2) /2, x0 = 2; 2) x = 2sint, y = 2 cost, t0 = /4.

167.1 ) y = 8 - 4x2, x0 = 1; 2) x = 2 cost, y = 2 2 sint, t0 = /4

168.1 ) y = (7 - x2) /2, x0 = 0.5 7; 2) x = 7 cost, y = 7/2 sint, t0 = /3.

169.1 ) y = 2(4 - x2), x0 = 1; 2) x = 2 sint, y = 2 2 cost, t0 = 5/6.

170.1 ) y = 4 - 8x2, x0 = 1/2; 2) x = 1/ 2 cost, y = 2 sint, t0 = 5/4.

 
<<     >>